Pengaruh Perilaku Konsumen Dan Persepsi Konsumen Tentang Produk Somethinc Terhadap Loyalitas Pelanggan - Herni Adriyati; Sunardi Sunardi (LPPM STIA Lancang Kuning Dumai, 2023)
The purpose of this study was to find out how customer and product satisfaction influence customer loyalty (a case study of somethink products on UIR students). The analysis used in this data is multiple linear regression analysis. The analysis tool used to assist the authors in processing the data is SPSS software version 24. The stages of processing the research start from testing the research instrument, testing the classical assumptions, analyzing data through multiple linear regression and ending with hypothesis testing. Based on the results obtained above, it can be seen that the coefficient of determination (R2) is 0.908 or 90.8%. Thus this value means that the customer and product satisfaction variables contribute 90.8% to UIR student customer loyalty while the remaining 9.2% is influenced by other variables not discussed in this study.